Dental caries profile in Monte Negro, Amazonian state of Rondônia, Brazil, in 2008 - Roosevelt Silva Bastos; Ricardo Pianta Rodrigues Silva; Adelson Francisco Maia-Junior; Fábio Silva Carvalho; Sabrina Merlini; Magali Lourdes Caldana; José Roberto Pereira Lauris; José Roberto Magalhães Bastos (University of São Paulo, 2010)
OBJECTIVE: This epidemiological survey assessed the dental caries profile in Monte Negro, a small town in the Amazonian state of Rondônia, Brazil, and its relationship with the northern region, national and global goals for oral health in the years 2000 and 2020. MATERIAL AND METHODS: The groups randomly examined were composed of individuals aged 5, 12, 15 to 19, 35 to 44, 65 to 74 years, living in both rural and urban areas. RESULTS: The means dft (standard deviation) and DMFT (standard deviation) for the groups were, respectively, 3.15 (3.12), 3.41 (2.69), 5.96 (4.19), 16.00 (7.30) and 25.96 (9.82). Caries-free individuals were 34.42%, 14.81% and 8.16% in the preschoolchildren, schoolchildren and adolescent groups, respectively. The Significant Caries Index percentages applied to the two younger groups were 6.65 and 6.70, and they increased to 32.00 in the individuals aged 65 to 74 years. Care Index percentages for adolescents, adults and elderly groups were, respectively, 29.40, 25.00 and 1.41. The dental caries profile in Monte Negro in 2008 shows that, 8 years after the year 2000, no FDI/WHO goal for any age settled in 1982 has been achieved. Dental caries increased with age and the main dental problem of adult and elderly groups was tooth loss. CONCLUSION: Oral health promotion and prevention of oral disease policies are urgent needs. Setting of oral health goals and targets to people living in Monte Negro or Amazonia to be pursuit and achieved in a near future is an important action to do because of the culture, sanitary conditions and socioeconomic aspects of this particular population.